Thinking about language teaching : selected articles 1982-2011. - Swan, Michael, 1936- (Oxford : University Press, 2012)
A selection of Michael Swan's best known published articles on the theory and practice of teaching English as a foreign language. Each article in this collection begins with a short introduction by Michael Swan explaining the context in which he originally wrote it. Consequently, the articles not only address topics that remain highly relevant to language teachers today, but also provide a historical perspective on developments within the field. The collection ends with a small selection of his published satirical pieces. * Contains eighteen academic and pedagogical articles and seven satirical pieces. * Brings Michael Swan's best known and most widely cited articles together in a single book for the first time. This creates a unique and valuable resource both for people already familiar with these articles and for those discovering them through this collection. * Articles were all originally published in leading journals such as Applied Linguistics and the English Language Teaching
Journal * All articles are published in their original form, but each one has an introduction by the author written specifically for this book, giving readers a historical and personal perspective on the topics discussed. * Suitable for a wide audience, including teacher trainers, practising and trainee teachers, as well as academics and researchers. What have been some of the most widely discussed themes and topics in the theory and practice of language teaching over the past thirty years? How much have things really changed during this period? This collection of articles by Michael Swan offers a uniquely personal view of trends and controversies within the teaching of English as a foreign language. They cover a wide range of topics, including: * the 'Communicative Approach' the drawbacks of 'one size fits all' solutions * the importance of prioritizing * the dangers of perfectionism * the importance of teaching at least some grammar * the need for various kinds of balance
(between form and function, student-directed and teacher-directed work, knowledge and skills, process and product, etc.) These and other issues are discussed and analysed in a clear, vigorous style by an author who has never been afraid to challenge prevailing opinions and practice. The book ends with a small collection of published satirical pieces. These show the author's more playful side, while at the same time furthering his broader aim of challenging conventional wisdom.
Keywords: Engels; Vreemde-talenonderwijs.